Security automaton to mitigate laser-based fault attacks on smart cards. (1st January 2014) - Bouffard, Guillaume; Thampi, Bhagyalekshmy N.; Lanet, Jean-Louis
Security and attacks are two sides of the same coin in the smart card industry. Smart cards are prone to different types of attacks to gain access to the assets stored in it and that can cause security issues. It is necessary to identify and exploit these attacks and implement appropriate countermeasures to mitigate their effects. Fault attacks are one among them. They can introduce abnormal behaviour on the smart card environment. The redundancy is necessary to detect this change in their environment. In this work, we propose an automatic method to obtain control flow redundancy using a security automaton to mitigate laser-based fault attacks and hence implement a smart card countermeasure based on the combination of static analysis and dynamic monitoring method. This is a very cost effective approach which can identify and mitigate the effects of fault attacks in an efficient way.